The mediating effect of 18F-FDG metabolism in right caudate between depressive symptoms and cognitive function in Alzheimer’s disease - Wang, Bojun; Cui, Chunlei; Chen, Yifan; Liang, Zhigang (Frontiers in Aging Neuroscience, 2024)
Purpose The objective of this study was to investigate the accumulation of 18F-fluorodeoxyglucose (18F-FDG) in the whole brain between Alzheimer’s disease (AD) with depressive (ADD) symptoms compared with AD without depressive (ADND) symptoms using positron emission tomography/magnetic resonance imaging (PET/MRI). Additionally, this study aimed to explore the associations among the accumulation of 18F-FDG in the brain, depressive symptoms, and cognitive function in ADD patients. Methods In this study, 25 AD patients and 22 healthy controls were enrolled. The AD patients were stratified into two groups, namely ADD and ADND, based on their scores of the Hamilton Depression Scale (HAMD). Both AD patients and healthy controls underwent an 18F-FDG PET/MRI scan. A standardized uptake value ratio (SUVR) was calculated to examine the accumulation of 18F-FDG in the brain. A simple mediation model was employed to examine the mediation effect between SUVR, depressive symptoms and cognitive function in ADD patients. Results The ADD group exhibited significant cognitive impairment compared to the ADND group (p < 0.001) and healthy controls (p < 0.001). The ADD patients exhibited the reduced SUVR (0.228 ± 0.126) in the right caudate (the voxel level p < 0.005, cluster level p < 0.05, after false discovery rate (FDR) correction) compared to ADND patients (0.459 ± 0.064) and healthy controls (0.706 ± 0.122). The SUVR of the right caudate was correlated with the HAMD scores (r = −0.792, p < 0.001) and mini-mental state examination (MMSE) (r = 0.738, p < 0.01). The relationship between depressive symptoms and the cognitive function in ADD patients is mediated by the right caudate SUVR (total effects = −0.385, direct effects = −0.02, total indirect effects = −0.405). Conclusion The ADD group exhibited the reduced SUVR in the right caudate compared to the ADND group and healthy controls. The relationship between depressive symptoms and the cognitive ability of AD patients was mediated by the right caudate SUVR. The results contribute to a deeper understanding of the neurobiological mechanisms related to AD with depressive symptoms.